PSYCHOPATHY OF KEVIN IN THE FILM WE NEED TO TALK ABOUT KEVIN (PSYCHOLOGICAL APPROACH) - Tian, Lestiana; Liru, Marianus W; Wanggai, Febe F I (Lantern: Journal of Language and Literature, 2024)
This study aimed at describing psychopathy symptoms of Kevin and at finding the factor causing Kevin become psychopath. This study was about individuals who were had psychopathy. The approach used in this research was a psychological approach and psychopathy theory to answer the research problem. This study used descriptive qualitative method.The result of this study indicates that there are five symptoms of psychopathy found in Kevin that are conning/manipulation, callous/lack of empathy, lack of remorse/guilt, impulsive, and irresponsible. Meanwhile, the factor causing Kevin becomes psychopath is parenting factor, because of the disapproval of a mother, namely Eva, in accepting Kevin’s presence while in her womb, then the way she adopted and educated Kevin so Kevin become naughty and committed criminal acts